Influence of Financial Literacy and Financial Behavior in Fundamentals of Accounting, Business and Management - Dumdum, Marlon; Vera, John De; Mangubat, Randy; Calasang, Veronica; Espina, Raymond (International Journal of Educational Studies, 2025)
This research assessed the financial literacy and mathematics performance of Grade 11 students. This research utilized a quantitative methodology, employing surveys to measure financial literacy in terms of financial decision-making, financial management, financial knowledge, financial planning and students’ behavior in terms of spending and saving habits. Students’ academic performance was also analyzed. A correlation analysis was conducted to test significant relationships between financial literacy and behavior constructs and learners’ academic performance. The findings revealed that students demonstrated moderate financial decision-making skills and positive saving habits. However, significant gaps were identified in financial management, financial knowledge, and financial planning. Academic performance in mathematics was consistently very satisfactory, showcasing a stable understanding of mathematical concepts. Correlation analysis indicated weak relationships between financial literacy constructs and mathematics performance, none of which were statistically significant. This suggests that financial literacy and mathematics skills are independent of one another in this context. The results highlight the need for targeted interventions to improve financial literacy, focusing on areas such as expense tracking, budgeting, and financial planning. Despite the lack of a significant relationship, enhancing financial literacy remains critical to preparing students for real-world financial challenges. The study provides valuable insights for educators and policymakers in developing programs to address gaps in financial literacy and foster responsible financial behaviors among students. Future research may explore alternative factors influencing financial literacy to better understand its broader implications.